Visualization and co-occurrence of journals in the area of information science in vis-a-vis the Qualis/Capes system in Brazil - Adilson Luiz Pinto; Alexandre Semeler-Ribas; Audilio Gonzales-Aguilar; Carole Clauzel (Netcom)
This paper aims at qualifying scientific journals that are part of the listing Qualis/Capes Brazil. The site of Capes only lists a few influential international titles. Included in this list are “Information Processing & Management, Organization Knowledge and Library” but several other important titles in Information Science are not covered. Our study describes 27 scientific worldwide journals, representing the world stage in Information Science, and which for some reason are not well respected in Brazil. The influence of these international journals (which are part of Web of Science) is evidenced by measuring the power they have in the scientific field of Information Science as well as the power of major authors (Salton, Spink, Nicholas, Belkin, Saracevic, Dervin, Garfield and others). Citation index comparison with the other journals in the area and index of impact factor are also analyzed. The results highlight the importance of JASIST, Information Processing & Management, College Research Library, Journal of Documentation, ARIST, Journal Information Sciences, Information Retrieval and Library Trends, both in the matter of world representativeness and in the number of citations.